FRI0267 Are worsening scleroderma capillaroscopic patterns associated with severe organ involvement in systemic sclerosis?: A pilot study. (23rd January 2014) - Smith, V.; Pizzorni, C.; Decuman, S.; Bonroy, C.; Van Praet, L.P.; Deschepper, E.; De Keyser, F.; Cutolo, M.
Abstract : Objectives: Assessment of associations of nailfold videocapillaroscopy (NVC) scleroderma patterns ("early", "active" and "late") with severe clinical involvement in a SSc population. Methods: 114 consecutive patients (Genova/Ghent) with SSc according to the LeRoy and Medsger criteria underwent nailfold videocapillaroscopic (NVC) assessment. Videocapillaroscopic images were classified into "normal", "early", "active" or "late" NVC pattern. Clinical evaluation was performed for 9 organ systems (general, peripheral vascular, skin, joint, muscle, gastrointestinal tract, lung, heart and kidney) according to the disease severity scale of Medsger (DSS) at baseline. Lung involvement was subcategorised into interstitial lung disease (ILD) and pulmonary arterial hypertension (PAH). Severe clinical involvement was defined as category 2-4 per organ of the DSS, or the presence of ILD or PAH. Logistic regression analysis with a NVC predictor variable was performed and odds ratios were calculated, where applicable. Results: NVC patterns were significantly associated with severe peripheral vascular (p<0.001), skin (p=0.002), joint (p=0.003), muscle (p<0.001), GI (p=0.038), lung (p<0.001) and heart (p=0.009) involvement. Clinical and significant odds ratios were found for peripheral vascular involvement and ILD. For peripheral vascular involvement 1/20 (=5%) of the patients with a "normal" or "early" pattern at baseline has a peripheral severe organ involvement, 11/44 (=25%) of the patients with an "active" pattern at baseline and 24/50 (=48%) of the patients with a "late" NVC scleroderma pattern. In simple/multiple (after correction for disease duration, LeRoy subset and vaso-active medication) logistic regression analysis, the estimated odds ratio to present severe peripheral organ involvement was stronger according to worsening NVC patterns (p<0.001/p=0.035). In this way the odds ratio for severe peripheral involvement was 3.36/2.18 (95% CI 1.77- 6.96/1.06-4.88) for the "active" and 11.27/4.77 for the "late" NVC scleroderma pattern versus the "normal" and "early" pattern. Concerning lung involvement, 50/114 (=44%) patients had ILD and 0 patients PAH. 1/20 (=5%) of the patients with a "normal" or "early" pattern at baseline has an ILD, 17/44 (=39%) of the patients with an "active" pattern at baseline and 32/50 (=64%) of the patients with a "late" NVC scleroderma pattern. In simple/multiple logistic regression analysis, the estimated odds ratio to present with ILD is stronger according to worsening NVC patterns (p<0.001/p<0.001). In this way the odds ratio for ILD is 3.99/4.31 (95% CI 2.18-7.87/2.07;9.87) for the "active" and 15.93/18.55 for the "late" NVC scleroderma pattern versus the "normal" and "early" pattern. Conclusions: This pilot study demonstrates an association between NVC patterns and severe peripheral vascular involvement and ILD, with a stronger odds of the "active" versus the "normal" or "early" pattern and an even stronger odds of the "late" pattern. These stronger odds according to worsening patterns indirectly validate the definitions of the scleroderma patterns. Disclosure of Interest: None Declared